A Screen of the Conserved Kinome for Negative Regulators of LIN-12 Negative Regulatory Region ("NRR")-Missense Activity in Caenorhabditis elegans. Issue 11 (1st November 2019) - Deng, Yuting; Luo, Katherine Leisan; Shaye, Daniel D; Greenwald, Iva
Abstract: Genetic analysis of LIN-12 /Notch signaling in C . elegans has provided many insights into human biology. Activating missense mutations in the Negative Regulatory Region (NRR) of the ectodomain of LIN-12 /Notch were first described in C. elegans, and similar mutations in human Notch were later found to cause T-cell acute lymphoblastic leukemia (T-ALL). The ubiquitin ligase sel-10 /Fbw7 is the prototype of a conserved negative regulator of lin-12 /Notch that was first defined by loss-of-function mutations that enhance lin-12 NRR-missense activity in C. elegans, and then demonstrated to regulate Notch activity in mammalian cells and to be a bona fide tumor suppressor in T-ALL. Here, we report the results of an RNAi screen of 248 C. elegans protein kinase-encoding genes with human orthologs for enhancement of a weakly activating NRR-missense mutation of lin-12 in the Vulval Precursor Cells. We identified, and validated, thirteen kinase genes whose loss led to increase lin-12 activity; eleven of these genes have never been implicated previously in regulating Notch activity in any system. Depleting the activity of five kinase genes ( cdk-8, wnk-1, kin-3, hpo-11, and mig-15 ) also significantly enhanced the activity of a transgene in which heterologous sequences drive expression of the untethered intracellular domain of LIN-12, suggesting that they increase the activity or stability of the signal-transducing form of LIN-12 /Notch. Precedents set by other regulators of lin-12 /Notch defined through genetic interactions in C. elegans suggest that this new set of genes may include negative regulators that are functionally relevant to mammalian development and cancer.